An Investigation of the Parental Mediation Situations of Preschool Children’s Parents - Yaman, Nihal Dulkadir; Karademir, Abdulhamit; Yaman, Fatih (My University, 2023)
Developments in information and communication technologies caused an increase in the possession of digital tools and facilitated their use. The use of digital tools, especially the internet, now starts below the age of two. In this sense, during early childhood, parents have a great responsibility as they are primarily responsible for their children’s “digital exposure.” They need mediation strategies to determine their children’s use of digital tools. This study aims to examine the parental mediation situations of the parents of preschool children. This study, conducted as a survey model, adapted the Parental Mediation Scale to the preschool level as a data collection tool. The participants of the study consisted of 108 parents of preschool children. The results of the study determined that the parental role (mother?father) and educational status of parents affected parental mediation strategies; whereas, the number of children, internet usage experience, income status, and the age of the parents or children did not affect said strategies. The qualitative analysis indicated that the parents have many concerns about the social?emotional and physical problems that may occur due to internet use in children from an early age. It is among the other qualitative results that parents prefer more direct intervention techniques and technical solutions to protect their children from the risks of the internet. As a result of the research, this study presents suggestions to parents and researchers for future studies on children’s conscious use of digital tools.